Annual Report on Exchange Arrangements and Exchange Restrictions 1961. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1961)
This paper discusses that total world trade rose significantly, particularly because of sustained European demand. With some exceptions, prices of basic products fell during the period. In this economic environment, developments in exchange markets became of focal interest to the IMF. The cumulative effect during recent years of relaxing surrender requirements and restrictions on payments has been very largely to restore to exchange markets their traditional function of reflecting the trend of international financial pressures. The difficulties that several countries faced in coordinating their internal and external monetary policies accentuated the international movements of short-term funds which had become increasingly important in preceding years. In particular, the Federal Republic of Germany and Switzerland received large amounts of foreign funds. Some countries continued to reduce their restrictions, particularly in the direction of simplifying exchange systems and liberalizing imports. These moves made a contribution toward sustaining the volume of world trade.